Facile access to pseudo-thio-1, 2-dimannoside, a new glycomimetic DC-SIGN antagonist. Issue 19 (1st October 2017) - Tamburrini, Alice; Achilli, Silvia; Vasile, Francesca; Sattin, Sara; Vivès, Corinne; Colombo, Cinzia; Fieschi, Franck; Bernardi, Anna
Graphical abstract: Abstract: The synthesis and conformational analysis of pseudo-thio-1, 2-dimannoside are described. This molecule mimics mannobioside (Manα(1, 2)Man) and is an analog of pseudo-1, 2-dimannoside, with expected increased stability to enzymatic hydrolysis. A short and efficient synthesis was developed based on an epoxide ring-opening reaction by a mannosyl thiolate, generated in situ from the corresponding thioacetate. NMR-NOESY studies supported by MM3 ∗ calculations showed that the pseudo-thio-1, 2-dimannoside shares the conformational behavior of the pseudo-1, 2-dimannoside and is a structural mimic of the natural disaccharide. Its affinity for DC-SIGN was measured by SPR and found to be comparable to the corresponding O -linked analog, offering good opportunities for further developments.